(untitled) (Revista Tópos, 2013)
O presente trabalho estuda a escada no ponto de vista arquitetônico (elementos, desenho, tipologia) e da segurança (normativo) e, logo, da prevenção a acidentes (investiga os índices), reunindo campos do conhecimento funcionalmente ligados, embora não seja costumeiro fazer uma ligação direta entre eles: a Arquitetura e a Medicina Preventiva. Apresenta a questão da adequação/inadequação dos espaços verticais de circulação, sobretudo as escadas, de forma a contribuir para que estas sejam espaços de trânsito seguro (embora instável), prevenindo a ocorrência de acidentes. Palavras-chave: espaço de circulação vertical, escadas, ergonomia. Abstract This paper studies the stair in the architectural point of view (elements, design, type) and security (normative) and so, the prevention of accidents (research indices), bringing together functionally related fields of knowledge, although it isn’t customary to direct connection between them: the Architecture and Preventive Medicine. It shows the problem of adequacy/inadequacy of vertical circulation spaces, especially the stairs, in order to contribute to these spaces are safe transit (though unstable), preventing the occurrence of accidents. Keywords: vertical circulation space, stairs, ergonomic.